Seed quality of rice cultivar MR 220 affected by different timing of harvesting / Abd Rahman Ansori Zainal Abidin - Zainal Abidin, Abd Rahman Ansori (Faculty of Plantation and Agrotechnology, 2018)
The study was to determine effect of harvesting time on rice (Oryza sativa) cultivar MR220 seed quality. The seed sample was collected at Bukit Lintang which directly harvested from field at three different timing (104,111 and 118 DAS). These seed sample were taken to seed laboratory and have been analyzed for its quality included fresh thousand seeds weight, seed moisture content, electrical conductivity and ability of fresh seed to germinate normally. Highest moisture content (MC) was obtained at 104 DAS (17.1%) compared to 111 DAS (14.3%) and 118 DAS (13.3%). Thousand seed fresh weight (TSW) was highest at 104 DAS (32.7 g) followed by 111 DAS (29.0 g) and 118 DAS (27.4 g) respectively. Electrical conductivity (EC) was measured at 118 DAS resulted the lowest reading 0.010 μs.cm-1g-1 meanwhile 0.033 μs.cm-1g-1 and 0.011 μs.cm-1g-1 respective harvested during 104 DAS and 111 DAS. Ability of fresh seed to germinate normally was obtained the highest percentage for seed lot of 118 DAS (86.5%) and the lowest was 77.0% at 104 DAS. In conclusion, the result showed that later in harvesting time influence rice seed quality particularly.